Did increased flooding during the African Humid Period force migration of modern humans from the Nile Valley?. (15th November 2021) - Zaki, Abdallah S.; King, Georgina E.; Haghipour, Negar; Giegengack, Robert; Watkins, Stephen E.; Gupta, Sanjeev; Schuster, Mathieu; Khairy, Hossam; Ahmed, Salah; El-Wakil, Mostafa; Eltayeb, Saleh A.; Herman, Frédéric; et al.
Abstract: During the Quaternary period, the eastern Sahara's hydroclimate oscillated between wet and dry intervals. These oscillations caused drastic changes in precipitation rates, often associated with ancient human migrations. In particular, significant migration of riparian populations from the Nile Valley to the west and northwestward of the Sahara occurred during the African Humid Period (AHP), an episode of increased monsoons, which characterized North Africa in response to increasing insolation. Several fossil rivers, now preserved as ridges throughout southern Egypt due to their floodplains' deflation, contain archeological artifacts and thus represent a potentially important record of fluvial activity during this episode of past human dynamics and environmental change. Here we present 14 C and Optically Stimulated Luminescence (OSL) ages of sediments preserved in these palaeorivers, which cluster within the AHP and are thus consistent with increased fluvial activity during this distinct humid period. Palaeohydraulic reconstructions based on grain size, channel geometry, and drainage area suggest typical precipitation intensities of 55–80 mm/h during sediment transport events. Given previous annual rainfall estimates, these hydrologic conditions may have lasted, or occurred, during the AHP up to 3–4 times more frequently than before and after this period. Such intense fluvial activity is consistent with monsoon intensification and may have rendered the area inhospitable for human settlements, congruent with population migration out of the Nile Valley during the AHP. These findings highlight links between past human ecodynamics and environmental signals, providing a concrete narrative of human population response to warming with potential echo in the current situation. Highlights: A chronological and palaeohydrological approach has been applied to six fossil rivers. Our chronological constraints cluster within the AHP (13–5.2 ka BP). Average rainfall intensity of 55–80 mm/h during channel sediment transport events occurred up to 3–4 times more frequently during the AHP. Human migration from the Nile Valley may have been driven by increased flooding for ca. 3000 years.